Dermatoglyphic and relation to the morphofunctional profile in professional male football club in Bogotá - Gálvez Pardo, Angela Yazmín; Cortés García, Anderson David; González Reina , Daniel Fabricio; Castro Jiménez, Laura Elizabeth; Argüello Gutierrez, Yenny Paola; Melo Buitrago, Paula Janyn (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
An optimal sports selection is formed by assessment of genotype (dermatoglyph) and phenotype (somatotype, body composition and physical abilities). The purpose of the study was to determine relationship between dermatoglyphics and morpho-functional profile in professional futsal athletes in the city Bogotá. The sample consisted of 12 men, who were anthropometrically evaluated, with a fat % of 18,4 ± 5,9; a musculoskeletal mass of 32,4 ± 4,4 kg and endo-mesomorphic somatotype. Through of dermatoglyphics, predominance was determined in the fingerprint designs L (69,2 ± 23,1), D10 (11,3 ± 3,6), SQTL (140,7 ± 95,1). Finally, explosive force was assessed with the Squat Jump test, in which the post position achieved the greatest height. In conclusion, there is a predisposition towards the physical capacities of speed, power, coordination and resistance, in addition the explosive force is greater in athletes with a lower value in endomorphic component and in percentage of fat mass.